(1164) optimum sample size for estimating dura crop yield rate in Sudan حجم العينة الأمثل لتقدير معدل إنتاج محصول دورا في السودان - abdel-razek, A. H.; hassan, abdel-azim (the institute of national planning, 2018)
the sudan is predominantly an agricultural country, agriculture is the main sector of its economy and its principal source of foreign exchange the government is building up most of its social and economical development programme and basing its external trade agreements on agriculture.